The Role of Sports Games Combined with English Education in Guiding Students' Psychological Transition - Bijun Hou; Jianshun Lu; Yanchun Liu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In order to understand the role of English education in guiding students' psychological transition, the author proposes a study based on sports games combined with English education to guide students' psychological transition. The author takes the practice of using sports games in English teaching at 10 universities in a certain province as the research object. A total of 300 questionnaires were distributed, 290 were collected, and 280 were valid. By searching for a large amount of literature and materials related to sports games both domestically and internationally in school libraries and the internet, the main focus is on psychology and the relationship between sports games and mental health. The experimental results indicate that students who frequently participate in sports games have better mental health levels than those who do not frequently participate in sports games and those who never participate in sports games, there are certain differences in depression, anxiety, hostility, and paranoia between students who participate in collective sports games and those who participate in individual sports games. From a cultural perspective, attaches great importance to examining the value of sports games, aiming to enhance people's understanding of sports games and promote students' mental health through sports games. Sports games play a very important role in school English teaching.